2012
DOI: 10.1024/0300-9831/a000098
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Conversion of ß-Carotene to Retinal in Bovine Rumen Fluid by a Recombinant ß-Carotene- 15, 15’-Monooxygenase

Abstract: Pasture-fed cattle yield carcasses with yellow fat; consumers often reject the resulting meat products because they assume they come from old and/or culled animals. Recombinant bacteria expressing beta-carotene 15, 15'-monooxygenase, introduced into the rumen of the animal, might help to reduce the coloration since this enzyme converts carotene to retinal, thereby eliminating the source of yellowness. The goal of this work was to evaluate the effect of a recombinant beta-carotene 15, 15'-monooxygenase (BCMO1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Studies in animal models and with cultured human malignant cell lines have demonstrated antitumor and anticancer activities of SE [11, 1419]. The mechanisms underlying cancer chemopreventive activities of SE include (i) inhibition of synthesis of DNA and RNA, but not protein [16]; (ii) ability to scavenge free radicals [20, 21]; (iii) involvement in the metabolic conversion of carotenoids to retinoids [22]; (iv) direct or indirect interactions with topoisomerase II [16]; (v) promotion of interactions mediated via lectins [23]; and (vi) downregulation of the expression of the catalytic subunit of the human telomerase, hTERT [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies in animal models and with cultured human malignant cell lines have demonstrated antitumor and anticancer activities of SE [11, 1419]. The mechanisms underlying cancer chemopreventive activities of SE include (i) inhibition of synthesis of DNA and RNA, but not protein [16]; (ii) ability to scavenge free radicals [20, 21]; (iii) involvement in the metabolic conversion of carotenoids to retinoids [22]; (iv) direct or indirect interactions with topoisomerase II [16]; (v) promotion of interactions mediated via lectins [23]; and (vi) downregulation of the expression of the catalytic subunit of the human telomerase, hTERT [24]. …”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of BCO1 and BCO2 from various organisms are summarized in Table 1. BCO1 derived from different sources (hereafter, BCO1s) are mainly found in animals, such as mammals [8,20,[26][27][28][29][30][33][34][35], chicken [22][23][24][25], Caenorhabditis elegans [21,44], and uncultured marine bacterium [32]. BCO2 derived from different sources (hereafter, BCO2s) have been reported in a wide range of organisms, including animals [11,15,[38][39][40], Saccharomyces cerevisiae [42], and plants such as apple [36], Arabidopsis thaliana [37], chrysanthemum [36], osmanthus [36], potato [41], rose [36], and saffron [43].…”
Section: Biochemical Properties Of Bco1 and Bco2mentioning
confidence: 99%
“…BCO1 derived from chicken, and expressed in E. coli, showed a higher specific activity than that expressed in BHK cells, indicating that activity of BCO seems to be affected by enzyme expression conditions such as the expression vector and host cells. For example, under the pBAD system, BCO activity was approximately 20 times higher than under the pET system [24,25]. On the other hand, purified human-derived BCO1, expressed in SF9 cells showed a higher specific activity and catalytic efficiency than that expressed in E. coli cells [8,29].…”
Section: Substrate Specificities Of Bco1 and Bco62mentioning
confidence: 99%
“…13,14 Good correlations in bioaccessibility have been found between in vitro studies and humans. 15 -17 Studies on bioaccessibility of SMM in human from food sources are not up to date. It could be very valuable to examine how SMM could be modulated under the human gastrointestinal (GI) tract.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro digestion systems, which simulate the human gastrointestinal tract, have been used for predicting digestive stability and bioaccessibility of a variety of micronutrients from fruits and vegetables . Good correlations in bioaccessibility have been found between in vitro studies and humans . Studies on bioaccessibility of SMM in human from food sources are not up to date.…”
Section: Introductionmentioning
confidence: 99%